2008
DOI: 10.1142/s0217979208047638
|View full text |Cite
|
Sign up to set email alerts
|

IMPROVEMENT IN MECHANICAL PROPERTIES OF Fe-Ni-Mn MARAGING STEEL BY HEAVY COLD ROLLING

Abstract: Maraging steels are a group of martensitic steels possessing ultra high strength along with good fracture toughness. Conventional 18 wt.% Ni maraging steels are very costly in part because of expensive alloying elements such as Ni and Co . Replacement of Ni by cheaper elements like Mn has been studied by many researchers. Fe – Ni – Mn ternary alloys show good age hardenability formation of nanometer sized intermetallic precipitates such as f.c.t. θ- NiMn during aging. These alloys are ductile in the solution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…However, recent studies (Hu et al, 2008;Leitner et al, 2011;Mahmoudi et al, 2011;Mahmudi et al, 2011;Nili-Ahmadabadi, 2008;Schnitzer et al, 2010;Sha et al, 2013) are being conducted in maraging steels without cobalt addition, in order to reduce the production costs of this alloy. Maraging steels are considered expensive due to their materials' preparation and expensive alloy elements such as nickel and cobalt processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies (Hu et al, 2008;Leitner et al, 2011;Mahmoudi et al, 2011;Mahmudi et al, 2011;Nili-Ahmadabadi, 2008;Schnitzer et al, 2010;Sha et al, 2013) are being conducted in maraging steels without cobalt addition, in order to reduce the production costs of this alloy. Maraging steels are considered expensive due to their materials' preparation and expensive alloy elements such as nickel and cobalt processes.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt is used only to minimize the solubility of molybdenum. In the case of maraging steel studied, this element was replaced by chrome, which besides improving the hardenability increases the corrosion resistance (Nili-Ahmadabadi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 represents the sequence of mechanical properties improvement from our previous work [16] to this research [29]. In our previous study, the maximum obtained elongation was 2.8% and maximum tensile strength was 1840 MPa for 90% cold rolled and aged sample while in as-annealed and aged condition has a premature fracture with zero ductility.…”
Section: Methodsmentioning
confidence: 73%
“…The nanostructured materials prepared by severe plastic deformation; receive larger strains that mean they could be the subject of different mechanical behaviors in analogy with conventional coarse-grained alloys [17][18][19][20][21][22][23][24][25][26][27][28]. To understand the origin of improved ductility, it was assumed the combination of cold rolling and wire drawing which leads to a larger strain in comparison with our previous work [16] and activate different deformation systems could be very useful steps to have nanograined materials and study any probable phase transformation. In this paper, we reported that the improvement of ductility in the Fe-10Ni-7Mn (wt.%) wire is likely attributed to ultra-grain refining and non-equilibrium austenite stabilization from bcc-martensite under large strain deformation and transformation of this austenite to -martensite in the nano-grained Fe-10Ni-7Mn (wt.%) martensitic steel during uniaxial tensile testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation